2022
DOI: 10.1111/jocn.16321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family beliefs and family strength on individual resilience and quality of life among young breast cancer survivors: A cross‐sectional study

Abstract: Aims and objectives: This study examines the effects of family beliefs and family strength on individual resilience and quality of life among young breast cancer survivors and determines whether family strength mediates the effect of family beliefs on individual resilience and quality of life. Background: Family beliefs and family strength are meaningful protective factors that help individuals maintain physical and mental health. However, few studies have explored their impact on individual resilience and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Furthermore, Tao et al. ( 87 ) revealed that 43.9% of patients with breast cancer were unemployed after diagnosis. Therefore, implementing various measures to promote the return of such patients to work and increase family income is crucial ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tao et al. ( 87 ) revealed that 43.9% of patients with breast cancer were unemployed after diagnosis. Therefore, implementing various measures to promote the return of such patients to work and increase family income is crucial ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…The support and positive beliefs of the family against breast cancer help in making the patient more flexible in the face of cancer complications and help to improve his quality of life (18).…”
Section: Discussionmentioning
confidence: 99%
“…If the family already had a deteriorating family health, created a worse starting point for coping with illness. Mobilizing family resources to establish healthy family beliefs will support cancer survivors' resilience and improve health‐related quality of life (Tao et al, 2022). Clinical implications should therefore focus to involve the family members from an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of family is described by Fernandes et al (2022) as something that generates a low quality in dealing with the strain that the disease puts on the family. Our ience and improve health-related quality of life (Tao et al, 2022).…”
Section: Ta B L E 4 Additional Quotes In Three Themesmentioning
confidence: 99%